Education on Drug and Its Danger to Adolescent Health in Laut Dendang Village Percut Sei Tuan District Deli Serdang: Edukasi Napza dan Bahayanya Bagi Kesehatan Remaja di Desa Laut Dendang Kecamatan Percut Sei Tuan Deli Serdang - Andarwati, Rini; Ismaniar Fauzi, Zulfa; Zulfikri, Zulfikri (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
The increasing trend of addictive substance use among young people is thought to be in line with the increasing pressure in all areas of life. Teenagers who are unable to deal with it can easily escape, gain pleasure and peace by using NAPZA. BNN uncovered 768 cases of narcotics crimes with 1,209 suspects. The purpose of this community service is to provide knowledge about NAPZA and its dangers to health to adolescents in Laut Dendang Village, Percut Sei Tuan District, Deli Serdang Regency. The methods used were distributing questionnaires before conducting counseling, providing education through lectures, video screenings and questions and answers, as well as providing pocket books and banners about the dangers of NAPZA and distributing questionnaires after counseling. From this community service, it was obtained that the knowledge of participants in the good category increased from 57.5% to 70% after education was carried out in the form of lectures and video screenings about NAPZA and its dangers to health.